Respostas

2014-06-26T23:24:15-03:00

A)
\frac{3x-2}{2}=\frac{5}{4} + \frac{2x+1}{8}\rightarrow \frac{12x-8}{8}=\frac{10+2x+1}{8}
 \rightarrow 10x = 19\rightarrow x = 1,9

B)
x^{2}=16 \rightarrow x = \sqrt{16}\rightarrow x=4

C)3x^{2}= 15x\rightarrow x^{2}= \frac{15x}{3}\rightarrow x^{2}= 5x\rightarrow x\cdot x= 5x\rightarrow x=\frac{5x}{x}\rightarrow x=5

D)(2x-1)^{2}= 0\rightarrow 2x^{2}-1=0\rightarrow 2x^{2}=1\rightarrow x^{2}=\frac{1}{2}\rightarrow x=\sqrt{\frac{1}{2}}

E)x^{2}-3x-10= 0\rightarrow x^{I}=5;x^{II}=-2

F) 3

espero ter ajudado

ajudou um pouco pois preciso de todas. Mas obrigada!
A melhor resposta!
2014-06-26T23:26:23-03:00
P) 4x² - x + 1 = x + 3 x²
   4x² - 3 x² - x - x +1 = 0
   x² - 2x + 1 = 0

a = 1
b = - 2
c = 1

b² - 4 a c 
(-2)² - 4. 1 . 1
4 - 4
  0

4/2 = 2           s= 2 , 2

q) 10 + x ( x-2) = 2
    10 + x² - 2x = 2
     x² - 2x +10 - 2 = 0
     x² - 2x + 8 = 0

a = 1
b = - 2
c = 8

b² - 4 a c 
(-2)² - 4 . 1 . 8
4 - 32
- 28           S = Ф

r) x ( x + 5) - 2x = 28
x² + 5x - 2x = 28
x² + 3x - 28

a = 1
b = 3
c = -28

b² - 4 a c 
3² - 4.1.(-28)
9 + 112
121

-3 +- √121/ 2
-3 +- 11 / 2
x1 = -3 + 11 / 2
x1 = 8/2
x1 = 4

x2 = -3 - 11 / 2
x2 = -14 / 2
x2 = -7                               s= 4, -7

s) (x - 1) (x - 5) = 7
    x² - 5x - 1x + 5 = 7
    x² - 6x +5 - 7 = 0
    x² - 6x -2 = 0

a = 1
b = -6
c = -2

b² - 4 a c 
(- 6)² - 4.1.(-2)
36 + 8
42

6 +- √42/ 2
x1 = 6 + √42 / 2
x1 = 3 + √42

x2 = 3 - √42

1 5 1